Air Pollution from Traffic at Major Causeway Al-Khobar, Saudi Arabia - Salama, Khaled F.; Zafar, Mubashir; Alrabea, Dulaim Abdullah; Alqahtani, Abdullah Ali; Almarghoub, Suhaib Abdulaziz; Alshehri, Ali Abdullah (Journal of Ecophysiology and Occupational Health, 2020)
Introduction: Causeway is providing a road link between travelers from Al-Khobar, Saudi Arabia and Bahrain. The vehicle traffic noise and emissions exhaust at Causeway have a significant effect on air quality parameters which leads to deteriorations impact on health of employees and passengers. The present study aimed to analyze the ambient air pollutants PM10, PM2.5, PM1, O3, CO2, SO2, CO, VOCs, and NO2, ambient noise and heat stress in and around causeway. Materials and Methods: All gaseous, particulate air pollutants, meteorological factors, ambient noise and heat stress were analyzed using standards calibrated equipment. July 2019 to October 2019 the study incused seven administrative sites in King Fahd causeway (Saudi Side). Air Quality Index (AQI) was used to determine the concentrations of selected ambient air pollutants. Results: All major air pollutants were high and significant difference in the concentration level between weekdays and weekends (p<0.05) and exceeds the international air quality guidelines in the selected studied sites of causeways. However, ambient noise demonstrated high significant levels in different studied sites in different times (p<0.05). Conclusion: Air quality measures in Causeway are significantly deteriorated and should be continuously evaluated to minimize the risk of daily exposure to traffic emissions.